MODERN METHODS OF PREVENTING IRON DEFICIENCY IN WOMEN AND CHILDREN (ON THE EXAMPLE OF TASHKENT REGION) - A.U.Ibragimov; J.J.Jalilov; A.I.Abrayqulov; Sh.I.Nuraliev; U.X.Xamidov (Scholar Express Journals, 2021)
This article scientifically substantiates and draws conclusions on modern methods of prevention of iron deficiency anemia in women and children living in the districts of Tashkent region
Keywords: Anemia; Iron Deficiency; Rational Nutrition; Decreased Hemoglobi; Blood Circulation